PENERAPAN MULTI ATTRIBUTE DECISION MAKING DALAM MEREKOMENDASIKAN OBJEK WISATA DI PULAU NUSA PENIDA - Ni Kadek Sukerti (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
The increase has also been influenced by the discovery of a number of new tourist attractions and maritime tours that are especially enjoyed by foreign tourists (diving and snorkeling). The location of the tourist attractions are not in one place but spread in several places with a considerable distance. If the vacation is only for one day, then the tourists must be able to choose attractions that line between the departing lane and the return lane so that it is more efficient. The data to be used in this study are internal and external data, alternatives that will be compared are a number of tourist sites with several criteria to be used. The method for processing data to be used is one of the methods in the Multi-Attribute Decision Making (MADM), the Technique for Order Preference by Similarity to Ideal Solution (Topsis) Method. This method is used to find weighted sums and performance ratings on each alternative on all attributes. Research methods carried out starting from literature studies, interviews, data analysis to be used, data processing with the method of Technique for Order Preference by Similarity to Ideal Solution (Topsis). The research is done in order to enable the tourists to determine the choice of tourist attractions that will be visited during their vacation on the island of Nusa Penida more easily. Based on the criteria and alternatives used, the study has resulted in having Angel Bilabong as the most visited tourist attraction with a total preference value of 0.6767285.